A comparative study of the lexical means of modality employed in culture and sport editorials of commendation on the USAtoday.com and the Vietnamnews.vn from 2010 to 2015 - Lê, Thị Thùy (2020)
The thesis analyzed the selected editorials of commendation on cultural and sporty fields chosen from the American English newspaper, the usatoday.com, and the Vietnamese English newspaper, the vietnamnews.vn, to identify the lexical means of modality employed in the two newspapers. The study aimed at analyzing how similar and different in tendencies of using modality as well as the functions of modality employed in commendation editorials in the two newspapers. The data showed that modality was realized in the two newspapers through modal auxiliary verbs, ‗knowledge‘ verbs, certain reporting verbs, modal adjectives and adverbs, and some modal nouns. From the findings, the research also provided some suggestions in teaching and learning English.